Civic Culture Administration to Push Forward Identity Ethnic of ‘Tai Song Dum’ in Thailand - Tangsripoolphon, Phumnawat; Jittaruttha, Chanida (Rajapark Journal, 2021)
This study is intended for the administration of citizen culture to drive factors that cause change and to study the ways to drive and maintain the identity of the Thai Song Dam ethnicity to be strong and sustainable. use a qualitative study of key informants involved. A total of 30 people were interviewed, and the tools used were an in-depth interview, structured interview form, and an observation form. The data was analyzed by content analysis. The results of the research were as follows: 1) Citizenship culture management in driving the identity of the Black Thai ethnicity in Thailand is currently systematic and orderly power management. There are different social positions and powers. 2) Factors causing this change in ethnic identity include the advancement of science and technology, the influence of the media. social media, immigration, educational progress, occupation, accepting culture from people outside the area, 3) Guidelines for driving and maintaining the Thai Song Dam ethnic group’s strong and sustainable identity, including promoting and supporting activities by the government and related agencies, as well as activities on the part of the Thai Song Dam ethnic group. They must instill in their children a sense of love and pride in their ethnicity. especially traditions and cultures in rituals, language, and dress.